Avaliação do “Em Frente Brasil” em São José dos Pinhais/PR (2019-2020) sob a ótica da economia do crime - Vasconcellos, Eduardo Palmeira (2022)
The objective of this thesis is to evaluate the performance of the pilot project Em Frente Brasil in the municipality of São José dos Pinhais from the year of 2019 to 2020. The project aimed to discourage violent crime. As there are several crimes that happen with the use of violence, this thesis was limited to analysing the rates of homicide and robbery, through the use of the technique of synthetic control, which is capable of generating a projection of what São José dos Pinhais would be like without the intervention of the pilot project Em Frente Brasil. Information and indicators referring to municipalities in Paraná with a population similar to São José dos Pinhais were used in order to generate this counterfactual. That means that the numbers of a population of over one hundred thousand inhabitants. This data was limited to the period from 2014 to 2020. The indicators used to generate the synthetic control were the GDP per capita and the IPARDES indices of municipal performance. The estimated population was used to select municipalities with a population of over 100,000 inhabitants. Though not used in the synthetic control as a variable. The thesis contributes to the literature by being the first to evaluate the aforementioned pilot project in Brazil. The results observed by the use of synthetic control show that the project did not make a significant contribution to the reduction of homicide and robbery rates, as the trajectory obtained by the counterfactual was a decrease in the respective rates, meaning that the reductions of these were also observed in other municipalities in Paraná that did not participate in the actions to fight violent crime in Em Frente Brasil. The observed reductions in homicide and robbery rates were part of a natural process that occurred in all the municipalities of Paraná observed in this thesis and not exactly the success of the pilot project Em Frente Brasil.